Pathologizing Subjecthoods: Pop Culture, Habits of Thought, and the Unmaking of Resistance Politics at Guantanamo Bay. Issue 3 (26th August 2014) - Beier, J. Marshall; Mutimer, David
Abstract : Beginning with a recurrent discussion about the choice between two imagined Star Trek technologies, the holodeck and the transporter, this article explores how popular culture can be revealing of ways in which political possibilities are variously made and foreclosed by dint of deeply held but underinterrogated ideational commitments circulating in the mundane and carried forward by what might seem unlikely voices. Tracing a few such commitments as they pertain to the legitimation and delegitimation of political subjecthood, we examine the political stakes of questions of agency and delusion through what were initially reported to have been the June 2006 suicides of three detainees at the US base at Guantanamo Bay, Cuba, and the crisis that emerged with respect to multiple hunger strikes at that same facility some seven years later. Through these we ask whether there might be resistance‐enabling possibilities as yet unimagined in agential choices that can so deeply offend prevailing sensibilities that it is sometimes difficult to abide them as valid choices at all. As we struggle with these resurgent security politics, it might seem frivolous to turn to film and television, or pub games at conferences, for guidance. What this article demonstrates is that these popular renderings of the limits of acceptable subjectivity draw on deep currents in our very broadest culture. In a very real sense, we are all very well prepared for our present political rendition.